Integration of Community pharmacy and pharmacists in primary health care policies in Argentina - Pedro D. Armando; Sonia A. Uema; Elena M. Vega (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Argentina is a federal republic with approximately 44 million people, divided into 23 provinces and an autonomous city, Buenos Aires. The health system is segmented into public, social security and private subsystems. The social security and private sectors cover more than 60% of the population. Total health expenditure in 2017 was 9.4% of gross domestic product. Primary health care (PHC) was considered as the principal strategy for universal coverage policy for health system reform in Latin America at the end of 20th century. The most remarkable characteristics of the Argentinian health system are its fragmentation and disorganization. An increase of public sector demands, due to a socioeconomic crisis, led to the subsequent collapse of the system, caused primarily by a sustained lack of investment. First care level decentralization to the Integral Health Service Delivery Networks (IHSDN) becomes the cornerstone of a PHC-based system. Pharmacists and community pharmacies are not formally mentioned in PHC policies or IHSDN. However, pharmacies are recognized as healthcare establishments as part of the first care level. Community pharmacists are the only health care professional whose profit comes from the margin on product sales. Contracts with social security and private insurances provide small margins which reduce the viability of community pharmacies. There is a preference by community pharmacies to diversify product sales instead of providing professional services. This is driven by marketing and economic pressures rather than patient care and health policies. Dispensing is the main professional activity followed by management of minor illness and associated product recommendations. Currently, there are no national practice guidelines or standard operating procedures for the provision of pharmaceutical services and there is no nationally agreed portfolio of services. National pharmacy organizations appear to have no official strategic statements or plans which would guide community pharmacies. There are some isolated experiences in community pharmacies and in public first care level pharmacies that demonstrate the possibilities and opportunities for implementing pharmaceutical services under the PHC approach. There is a real lack of integration of community pharmacies and pharmacists in the healthcare system.